EVALUASI DATA KEDALAMAN LAUT DARI CITRA LANDSAT 7 ETM+ (Studi Kasus Perairan Pantai Sadeng, Yogyakarta) - , PAOLO TUANAKOTTA SRG ([Yogyakarta] : Universitas Gadjah Mada, 2013)
One way to generate the source data on the depth of the sea is to use remote sensing technology. This technology can simplify the presentation of ocean depth data of the water without having to make direct measurements in the field. One method that is often used to generate ocean depth data is to use Juppâs method. This method has been used to generate data on the depth of Kepulauan Seribu, where the characteristic is relatively shallow waters. This study applied Juppâs method to generate depth data on areas where the waters of Sadeng relatively dynamic. This research began of this research is radiometric and geometric correction of the Landsat 7 ETM + imagery, the boundary of land and water is used masking formulas and training area determination with reference to the National Marine Environment map. After the process, the depth zone of penetration (DOP) is determined, each depth decided using the statistical value of each band. Furthermore, interpolate the regional penetration, image classification and analysis of the results by measuring the number of pixels of ocean depth data of Landsat 7 ETM + which is overlap with the reference data of GEBCO. Depth result of the image is symbolized by the color and depth data of GEBCO symbolized by a polygon between depth contours . The results shows the depth data of Landsat 7 ETM + imagery of Sadeng less accurate. This is indicated by the ratio of the number of pixels of the image depth that overlap the GEBCO depth data that are not consistent. With in depth range of 0 to 1 meter according to Jupp depth definition, GEBCO depth data agrees 42,2%, while depth data generate from image only agrees 15,6%. Depth range of 1 to 5 meters according to Jupp depth definition, GEBCO depth data agrees 43,9%, while depth data generate from image only agrees 2,1%. Depth range of 5 to 15 meters according to Jupp depth definition, GEBCO depth data agrees 22,3%, while depth data generate from image only agrees 13,9%. Depth range of 15 to 25 meter according to Jupp depth definition, GEBCO depth data agrees 89,9%, while depth data generate from image only agrees 2,9%. Hence, ocean depth generated from Landsat 7 ETM image over dynamic ocean water is not accurate.